Impact of 3-D Printing Technology in Manufacturing Supply Lines to Improve Resilience During Black Swan Events - Ajay Serohi (International Journal of Supply Chain Management, 2021)
AbstractPurpose: Globalized networks of suppliers and manufacturing hubs may fail in the face of high impact and unpredictable events such as Hurricane Katrina, the 9/11 terrorist attack, the Fukushima disaster and the COVID-19 pandemic—known as black swan events. I examine how 3-D printing, a now widespread and powerful technology, may be relevant in this context.Originality: I show 3-D printing in the manufacturing sector will simplify complex and globalized networks thereby making them more resilient to black swan events. The findings of this review article are important for managers and chief supply chain officers in that they can better simplify the chains through the adoption of 3-D printing infrastructure, thereby insulating their businesses from the cascading effects of black swan events.Design/ Methodology/ Approach: The study looks into secondary data (collected from authentic data sources both public and private) sources. The thorough literature review to examine how the design of supply networks can be simplified to improve resilience to black swan events through the use of 3-D printing helps to better substantiate our argument.Findings: I find support for the hypothesis that the adoption of 3-D printing infrastructure in manufacturing supply chain infrastructure leads to simplification of the networks. It facilitates simplification through economies of scale, customization, co-production, better demand prediction, freedom in shape design, allowance for manufacturing postponement, fewer nodes and integration of functionalities to reduce steps in the chain. These contribute to improved resilience through a variety of mechanisms.